FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PAJAK EFEKTIF - Andang Wicaksono, 11.05.52.0138; Kartika, Andi (Students Journal of Accounting and Banking, 2015)
Nowadays many companies want to do tax planning in order to decrease their tax burden. The result of tax planning can be measured by effective tax rate. This research examines the effect of firm size, firm leverage, capital intensity, and inventory intensity on effective tax rate. This research was conducted at the manufacturing companies listed in the Indonesian Stock Exchange. The sampling method used purposive sampling with the observation period from 2009 to 2013. The results indicated that firm size has significant negative effect on the effective tax rate, while capital intensity and intensity inventory has the opposite effect. This study also showed that firm leverage does not significantly affect the effective tax rate.Keywords: Effective Tax Rate, Firm Size, Firm Leverage, Capital Intensity, Inventory Intensity